Formulas of General Solution for Linear System from Ordinary Differential Equations by Using Novel Transformation (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, we use Novel transform which has the form  to solve a system of linear differential equations, while homogeneous or non-homogeneous system. Moreover, general formula of the set solution of systems of first and second order are derived.